2005
DOI: 10.1111/j.1365-2796.2005.01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and imaging cardiac repolarization abnormalities

Abstract: Abstract. Rudy Y (Washington University in St Louis, St Louis, MO, USA). Modelling and imaging cardiac repolarization abnormalities. J Intern Med 2006; 259: 91-106. Repolarization abnormalities, including those induced by the congenital or acquired long QT (LQT) syndrome, provide a substrate for lifethreatening cardiac arrhythmias. In this article, we use computational biology to link HERG mutations mechanistically to the resulting abnormalities of the whole-cell action potential. We study how the kinetic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This force-frequency dependence arises even in the absence of β-adrenergic stimulation, as evidenced by the observation that in isolated myocytes fast pacing leads to a greater calcium transient (CaT) amplitude and increased force of contraction (Wang et al 1988). The CaMKII signaling cascade is likely to be involved in this process, because it has been shown to interact with the cell machinery that generates the CaT (Maier & Bers, 2002;Hund & Rudy, 2004,2006Zhang et al 2005). Specifically, CaMKII substrates include I Ca(L) , the ryanodine receptor (RyR), the SR Ca 2+ -uptake pump (SERCA2a) and phospholamban (PLB) (Le Peuch et al 1979;Wegener et al 1989;Witcher et al 1991;Toyofuku et al 1994;Yuan & Bers, 1994;Odermatt et al 1996;Hagemann et al 2000).…”
Section: Camkii Regulation Of the Ca 2+ Transientmentioning
confidence: 99%
“…This force-frequency dependence arises even in the absence of β-adrenergic stimulation, as evidenced by the observation that in isolated myocytes fast pacing leads to a greater calcium transient (CaT) amplitude and increased force of contraction (Wang et al 1988). The CaMKII signaling cascade is likely to be involved in this process, because it has been shown to interact with the cell machinery that generates the CaT (Maier & Bers, 2002;Hund & Rudy, 2004,2006Zhang et al 2005). Specifically, CaMKII substrates include I Ca(L) , the ryanodine receptor (RyR), the SR Ca 2+ -uptake pump (SERCA2a) and phospholamban (PLB) (Le Peuch et al 1979;Wegener et al 1989;Witcher et al 1991;Toyofuku et al 1994;Yuan & Bers, 1994;Odermatt et al 1996;Hagemann et al 2000).…”
Section: Camkii Regulation Of the Ca 2+ Transientmentioning
confidence: 99%
“…Decreased repolarization reserve results from augmented inward and/or diminished outward currents during the late phase of the AP plateau, so that small increases in inward currents, classically mediated by reactivation of the L-type Ca (I Ca,L ) window current (7,8,27,31,38), can reverse repolarization to create an EAD. EADs are often exacerbated by bradycardia because more complete deactivation of K channels into deeply closed states during diastole further decreases systolic repolarization reserve (23). As such, the role of EADs as triggers of cardiac arrhythmias has received greater emphasis than their potential effects on destabilization of already established reentry.…”
mentioning
confidence: 99%
“…While EADs are known to occur under conditions of reduced repolarization reserve, such as the various LQT syndromes, they usually require further reduction of repolarization reserve via rate-dependent mechanisms. Under conditions of bradycardia, repolarization reserve is reduced by more complete deactivation of outward K currents during long diastolic intervals [29]. Under conditions of tachycardia, we found that repolarization reserve is reduced by larger Ca-sensitive inward currents during the AP plateau, which in this model is caused by a larger overall Ca i transient when the J spon -triggered release summated with the AP-triggered, I CaL -gated CICR.…”
Section: Discussionmentioning
confidence: 68%